Rabies Symptoms, Diagnosis, Prophylaxis and Treatment - Charles Rupprecht (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Rabies is an acute, progressive, incurable viral encephalitis and one of the oldest described infectious diseases. All mammals are susceptible to infection, but rabid dogs are responsible for the greatest global burden. Bats and carnivores are the major wildlife reservoirs. More than 60,000 persons, primarily children, succumb each year after the bite from a rabid animal. This compilation describes new information on disease surveillance, diagnosis, prevention and control within Africa, Eurasia and the New World. Public health professionals, veterinarians, physicians, laboratory workers and conservation biologists should appreciate the novel communications provided from internationally renowned authors and the diversity of topics in this special issue on rabies.